How Russian Hackers and Trolls Exploited U.S. Media in 2016. - JAMIESON, KATHLEEN HALL (Proceedings of the American Philosophical Society, 2019)
The article focuses on ways in which agents of the Russian government, manipulating social media like Facebook and Twitter, actively worked to disrupt the 2016 election. It mentions power has been confirmed in studies demonstrating the relationship between the most-often-covered issues and what the audience considers important. It also mentions interlopers assumed guises that shielded their true identity as they marauded about in cyberspace.